Pengaruh Persepsi Harga, Kualitas Produk, dan Lokasi Terhadap Keputusan Pembelian Pada Outlet SaladCuyy Bojonggede - Budhi Santoso; Verry Cyasmoro (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
This study aims to analyze the effect of perceived price, product quality, and location on purchasing decisions at SaladCuyy Bojonggede outlets with quantitative methods. The data in this study used primary data obtained by randomly distributing questionnaires to 100 SaladCuyy Bojonggede consumers using incidental sampling techniques. The data analysis technique in this study used a multiple linear regression model supported by the classical assumption test, multiple linear regression test, test the coefficient of determination, and hypothesis testing with the t test and f test. The results of this study stated that only the location variable had no significant effect on purchasing decisions at SaladCuyy Bojonggede outlets. However, the perception of price and product quality has a positive and significant effect on purchasing decisions at SaladCuyy Bojonggede outlets. The findings from this study indicate that SaladCuyy Bojonggede outlets need to pay attention to product prices and product quality to increase sales of the SaladCuyy Bojonggede outlet products.